Analysis of Good Corporate Governance in Increasing Investor Trust - Safitri, Tsamara Nayla; Athaya, Nada Syifa; Miranda, Aqilah; Maisyarah, Renny (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2025)
This study aims to examine in depth the role of Good Corporate Governance (GCG) in increasing investor confidence in public companies. Investor trust is an important element that can influence investment decisions and long-term loyalty. Using a descriptive qualitative approach through a literature study, this research collected secondary data from various sources such as scientific journals, books, international regulatory reports (OECD), as well as local policies from the Financial Services Authority (OJK). The analysis was conducted by highlighting how the implementation of GCG principles-such as transparency, accountability, responsibility, independence, and fairness-contributes to improving managerial integrity and corporate credibility in the eyes of investors. The results show that companies that consistently implement GCG principles have higher attractiveness in the capital market, and are able to create a more stable and sustainable investment climate.